STRATEGI BISNIS PT. POS INDONESIA - Irwan Chaeruddin; Eka Musdalifah (Institut Transportasi dan Logistik Trisakti, 2016)
PT. Pos Indonesia is a company focusing on the delivery of packages and documents worldwide. Now we know that many courier companies and forwarding serve delivery services. So that PT. Pos Indonesia can survive amid competition, the author will formulate a strategy. But earlier, the authors need to analyze internal and external factors. The author will use a SWOT analysis to complete this study. This method is quite flexible in various state companies. The results of this study PT. Pos Indonesia are advised to use its strength to deal with the threats and opportunities. The strategies implemented by utilizing the factors of internal forces that exist to grab opportunities PT. Pos Indonesia in order to increase business. Based on the author analysis, an IFE score of 2.35 and EFE score of 2.24 and be in quadrant V, stability.